2013
DOI: 10.4172/2155-9546.1000192
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive Value of Diets Containing Digeston-1 as a Feed Additive for Nile Tilapia (Oreochromis niloticus) Fingerlings

Abstract: Digeston-1 (fermented soybean meal) is produced by controlled lactic acid fermentation with natural lactic acid bacteria. In the present study, a total of 150 fish with average initial body weight 10.11 g were randomly stocked into 15 aquaria to study the effect of Digeston-1 on performance and growth parameters of Nile tilapia (Oreochromis niloticus) fingerlings. Results revealed that the group fed diet contain Digeston-1 recorded the highest (P<0.05) growth parameters in terms of final body weight gain, aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
(27 reference statements)
4
10
0
Order By: Relevance
“…Average of CP was found to be a significantly (P<0.05) different among experimental groups .The highest value of crude protein contents was recorded in T5 (58.40%) while the lowest value of crude protein contents was recorded in T1 (56.49. These results in agreement with the finding of Khalafalla (2013) for Nile tilapia (Oreochromis niloticus ). …”
Section: Whole Body Compositionsupporting
confidence: 92%
See 2 more Smart Citations
“…Average of CP was found to be a significantly (P<0.05) different among experimental groups .The highest value of crude protein contents was recorded in T5 (58.40%) while the lowest value of crude protein contents was recorded in T1 (56.49. These results in agreement with the finding of Khalafalla (2013) for Nile tilapia (Oreochromis niloticus ). …”
Section: Whole Body Compositionsupporting
confidence: 92%
“…These results are in agreement with Hammed (2012) for fingerlings African catfish, Clarias gariepinus. And, also Khalafalla (2013) when was used Digeston-1 (fermented soybean meal) for Nile tilapia (Oreochromis niloticus) fingerlings at level (0.5% and 0.7%). Table (2) showed that treatment applied had no effect on survival rate throughout the experimental period.…”
Section: Growth Performancementioning
confidence: 99%
See 1 more Smart Citation
“…These results are in agreement with Hammed (2012) for fingerlings African catfish, Clarias gariepinus. Also Khalafalla (2013) and Noaman et al (2015). It was found that fermentation of soybean meal induced removal or inactivation of anti-nutritional factors (Lim et al, 2010), improvement of the nutritional quality (Canella et al, 1984), improvement of digestibility (Kiers et al, 2000) and shelf life of the processed food (Skrede and Nes, 1988).…”
Section: Growth Performancementioning
confidence: 94%
“…These biological agents have been utilized for disease control, supplements to improve growth, and in some cases as a means of replacing antimicrobial compounds in aquaculture. Probiotics have proven to inhibit the growth of pathogens through production of antagonistic compounds, competition for attachment sites, nutrients, and alterations of enzymatic activity of pathogens, immune-stimulatory functions, and nutritional benefits such as improvement in digestibility and utilization in feed [10]. Hence, the concept of utilizing probiotics in animal feed, particularly, poultry and fish, is fast gaining acceptance [11].…”
Section: Introductionmentioning
confidence: 99%